The Influence of Content Marketing and Product Knowledge on Generation Z Purchase Intention in Using Bank Syariah Indonesia services - Nora Aulya Shalsabilah; Fani Firmansyah (Universitas Negeri Padang, 2023)
This study aims to find out how the correlation between content marketing and product knowledge and its impact on Generation Z's purchase intention towards Indonesian Sharia Banks. Data collection was carried out by distributing questionnaires to Generation Z students at UIN Maulana Malik Ibrahim Malang. This study adopts a quantitative approach with an explanatory design. Purposive sampling was used as a sampling technique, with a total sample of 100 participants. The measurement scale uses a Likert scale with five response levels. Data analysis includes validity tests, reliability tests, classical assumption tests, multiple linear regression analyses, t tests, F tests, and coefficient of determination tests using SPSS version 26. The findings demonstrate that content marketing variables exert a significant influence on purchase intention, product knowledge variables have a significant impact on purchase intention, and both content marketing and product knowledge together significantly influence purchase intention.